Penatalaksanaan Infrared Dan Chest Physiotherapy Pada PPOK Eksaserbasi Akut Di BBKPM Surakarta - Wardani, Chori Nila; , Isnaini Herawati, SSt., FT., M. Sc (2014)
Background: Scientific paper on the physiotherapy management of pulmonary disease Acute Exacerbation of Chronic Obstuksi at Surakarta BBKPM is intended to provide knowledge, information and understanding about the condition of Chronic Obstructive Pulmonary Disease which causes many physical problems associated with respiratory disorders and modalities are given on the condition this is infrared and chest physiotherapy (breathing exercise, coughing exercise)Purpose: Scientific paper aims to determine the benefits of infrared and chest physiotherapy (breathing exercise, coughing exercise) in the case of Chronic Obstructive Pulmonary Disease useful to reduce/eliminate shortness of breath, cough and sputum sample streamline, improve/change the thoracic expansion and increase functional activity Methods: A case study and the provision of infrared, chest physiotherapy (breathing exercise, coughing exercise) after the treatment much as 6 X then obtained results Results: The frequency of shortness of breath decreases measured by borg scale in the early physiotherapy (T1): 3 (moderate tightness) and the end of the physiotherapy into (T6): 2 (lightly packed). An increase in the effectiveness of cough and sputum spending at the start of physiotherapy (T1): non-productive, do not remove phlegm and became (T6): productive remove phlegm at the end of physiotherapy. Increased mobility of the thoracic cage towards good for inspiration and expiration process and the normal maximum at the start of physiotherapy (T1): axilla 2 cm, inter costalis IV 1.5 cm and 1.5 cm xypoideus prosessus and end physiotherapy (T6): axilla 2 cm, inter costalis IV 1.5 cm and 2 cm prosessus xypoideus. And also an increase in the ability of the functional activity of early physiotherapy (T1): 3 personal hygiene, household activities 4, physical activity 4, recreation activities 3, general 3 and the final general physiotherapy (T6): 1 personal hygiene, household activities 1, 2 physical activity, recreation activities 1, general 1Conclusions and suggestions: from the above results it can be concluded that there is success in helping to decrease shortness of breath. An increase in the effective cough and sputum expenditure. Increased mobilization of the thoracic cage is certainly a good direction. The ability of functional activity increased so that the patient can perform their own activities. The next suggestion is better maintain the health condition of the patient and the environment around the house